Modeling of Paleohydrologic Change during Deglaciation - Maizels, Judith (Géographie physique et Quaternaire, 1986)
ABSTRACTThis paper aims to test whether estimates of paleodischarge made for proglacial terrace sequences support the model of largescale change in hydrologic regime (as inferred from channel pattern, form and sedimentology changes), during deglaciation. Modeling paleodischarges of former braided stream systems on each terrace surface is shown to be at a tentative stage, however, because of numerous error sources and assumptions that remain to be tested. These are discussed in relation to field measurements of channel width, depth, gradient and sedimentology; to theoretical modeling of flow depth, resistance coefficients, velocity, Froude number and discharge; and to geomorphic interpretation of the flow events being modeled. The different discharge models adopted have provided approximate estimates of former peak flows and patterns of change in peak flow magnitudes during deglaciation. Longterm deglaciation appears to have been associated with largescale decreases in peak flows of between 10 and 30 times. On shorter timescales, peak flows produced by short-term meltwater and by non-melt processes, such as volcanically induced floods, mask any longer term discharge trends in the catchment.